Applying the New Autosampler to Enter the Equilibrium Gas Phase TriPlus 500 (Thermo Scientific) for the Analysis of Residual Solvents According to USP Method <467> - article Editorial (Разработка и регистрация лекарственных средств)
Organic solvents are widely used in the synthesis of pharmaceutical products and cannot always be completely removed during the manufacturing process. To ensure safety, the end products are tested for the residual content of solvents used in manufacturing processes, how efficiently they are removed or, if they are still present, whether their concentration is within acceptable limits. The results presented in this paper demonstrate that the new TriPlus 500 HS autosampler, combined with the Trace 1310 GC and FID detector, provides the performance needed for the analysis of residual solvents in pharmaceutical products, meeting or exceeding USP <467> method requirements.